A supported catalyst, preparation method and application thereof in the synthesis of indole, carbazole and derivatives
The catalyst formed by the loading of CuO and additive metal on copper-aluminum spinel solves the problem of high catalyst cost and easy sintering and inactivation in the prior art, and achieves efficient and stable synthesis of indole and carbazole, which is suitable for industrial applications.
Patent Information
- Application Number
- CN202411676387.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-11-22
AI Technical Summary
In the prior art, the catalyst for synthesis of indole compounds has high cost and complex structure, and the Taman temperature of copper elements is low, which leads to the catalyst being easily sintered and inactivated, with a short service life, making it difficult to achieve continuous operation.
The supported catalyst formed by CuO and additive metals are prepared by co-precipitation and calcination. The mass proportion of CuO is 10%-30%, the mass proportion of copper-aluminum spinel is 65%-85%, and the additive metals are Mg, Zn, Ce, Zr, Mo, La, Y, Cr, Ni or Co.
This catalyst has excellent activity and long service life, can effectively synthesize indole, carbazole and derivatives, and has low production cost, making it suitable for industrial applications.
Smart Images

Figure CN119175097B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical production raw material preparation, and in particular to a supported catalyst, a preparation method and application thereof in the synthesis of indole, carbazole and derivatives. Background Art
[0002] With the development of the economy and society, the status and role of fine chemical products in the national economy have become increasingly prominent. As an important fine chemical intermediate, indole compounds are important raw materials for the production of spices, printing and dyeing, and for the prevention and treatment of cardiovascular diseases, neurological diseases, tumors, and immune-enhancing drugs. Initially, indole produced industrially was usually separated from coal tar, and the content in the 220 ℃ ~ 270 ℃ fraction was about 2% ~ 3%. However, due to the difficulty in separation, high energy consumption, and complex refining process, the cost of indole compounds is high. In addition, a large number of pollutants will be generated during the reaction, which will pollute the environment. In recent years, due to people's attention to indole compounds, the synthesis of indole compounds has been widely studied. A large number of organic synthesis methods, such as nucleophilic cyclization and electrophilic cyclization, are applied to the synthesis of indole compounds. However, since the selected catalysts are all multi-component catalysis, the main catalyst has a complex structure, a complex preparation process, and is expensive, further optimization research is needed before industrial production.
[0003] The alcohol amine method, which uses aniline and ethylene glycol as raw materials to synthesize indole in one step, is a relatively economical method among many indole derivative synthesis methods. The raw materials are cheap, the steps are simple, and the byproducts are water and hydrogen. The harm to the environment is greatly reduced, and it is also very practical for further expansion to industrial applications. The key lies in the research and development of catalysts. For this reaction, the catalysts used are generally precious metal catalysts, which are expensive and complex in structure. Among non-precious metal catalysts, copper-based catalysts have been widely studied due to their high activity and low price. Researchers loaded different amounts of copper on carriers such as SiO2 and γ-Al2O3, and then added elements such as Mg, Zn, and Mn to improve the activity of the catalyst. However, due to the low Tamman temperature of copper, it is easy to sinter and deactivate at the reaction temperature, and the catalyst has a low service life, making it difficult to achieve continuous operation.
[0004] In addition, another important nitrogen-containing heterocyclic ring, carbazole, is an important skeleton for organic synthesis and has a variety of biological and synthetic applications. It exhibits many biological activities such as antibacterial, anticancer, anti-inflammatory, and antiviral. The carbazole skeleton has potential application prospects in fluorescent probes, bioimaging equipment, organic semiconductors, and polymers. However, there are few reports on the synthesis catalysts used in the technical route of synthesizing carbazole by the alcoholamine method. Summary of the invention
[0005] In view of the above problems existing in the prior art, the present invention provides a supported catalyst, a preparation method and application thereof in the synthesis of indole, carbazole and derivatives. The supported catalyst has low preparation cost and can be used for synthesizing indole, indole derivatives and carbazole and derivatives by the alcoholamine method with good yield.
[0006] The specific content of the invention is as follows:
[0007] In a first aspect, the present invention provides a supported catalyst, wherein the supported catalyst is formed by supporting CuO and an auxiliary metal on copper aluminum spinel, wherein the auxiliary metal is Mg, Zn, Ce, Zr, Mo, La, Y, Cr, Ni or Co, with a mass proportion of 0 to 10%; the mass proportion of CuO is 10% to 30%; and the mass proportion of copper aluminum spinel is 65% to 85%.
[0008] Optionally, in the supported catalyst, when the mass proportion of the auxiliary metal is 0, the mass proportion of CuO is 17% to 27%; and the mass proportion of the copper-aluminum spinel is 70% to 84%.
[0009] Optionally, in the supported catalyst, the mass proportion of the auxiliary metal is 0.4% to 4%; the mass proportion of CuO is 18% to 25%; and the mass proportion of the copper aluminum spinel is 68% to 78%.
[0010] In a second aspect, the present invention provides a method for preparing the supported catalyst according to the first aspect, the method comprising:
[0011] Dissolving a copper precursor, an aluminum precursor, and an auxiliary metal precursor in a solvent in a certain proportion to form a mixed system;
[0012] Adding alkaline solution to the mixed system, adjusting the pH of the system to 9-11, aging for 12 h-24 h, collecting the solid by centrifugation, washing and drying to obtain a catalyst precursor;
[0013] Grinding the catalyst precursor, placing it in a muffle furnace, and calcining it at 600° C. to 1000° C. for 1 h to 6 h to obtain the supported catalyst;
[0014] The precursor of copper is Cu(NO3)2·3H2O; the precursor of aluminum is Al(NO3)3·9H2O; the precursor of auxiliary metal is a soluble salt containing Mg, Zn, Ce, Zr, Mo, La, Y, Cr, Ni or Co.
[0015] Optionally, in the mixed system, the molar ratio of copper ions, aluminum ions and auxiliary metal ions is 1:1:0 to 1:3:0.1;
[0016] The concentration of total metal cations is 0.25 mol / L to 2 mol / L.
[0017] Optionally, the solvent is deionized water, or the solvent is an aqueous solution containing hexadecyltrimethylammonium chloride.
[0018] Optionally, in the mixed system, the molar ratio of the hexadecyltrimethylammonium chloride to the total metal cations is 0 to 0.1:1.
[0019] Optionally, the soluble salts include nitrates, sulfates, acetates, chlorides or ammonium salts.
[0020] Optionally, the alkali solution is a sodium carbonate solution, a sodium hydroxide solution or an ammonia solution.
[0021] In a third aspect, the present invention provides an application of the supported catalyst described in the first aspect, wherein the supported catalyst is used as a catalyst for synthesizing indole, carbazole and derivatives by an alcoholamine process.
[0022] Optionally, in the reaction raw materials for synthesizing indole, carbazole and derivatives by the alcoholamine method, the molar ratio of amine to alcohol is 3:1 to 9:1, the raw alcohol includes ethylene glycol, 1,2-propylene glycol, glycerol or 1,2-cyclohexanediol, and the raw amine includes aniline, N-ethylaniline, o-methylaniline, m-methylaniline, p-methylaniline or N-methylaniline;
[0023] The process conditions for synthesizing indole and its derivatives by the alcoholamine method include: a reaction temperature of 250°C to 330°C; a feed space velocity of 0.1 h -1 ~2.0 h -1 ;
[0024] The process conditions for synthesizing carbazole and its derivatives by the alcoholamine method include: a reaction temperature of 280°C to 380°C; a reaction raw material feed space velocity of 0.1 h -1 ~2.0 h -1 .
[0025] Optionally, before the reaction raw materials are introduced, the supported catalyst loaded into the reactor is reduced and activated at 150° C. to 200° C. for 1 h to 3 h in a nitrogen and hydrogen mixed atmosphere containing 1% to 20% hydrogen.
[0026] Compared with the prior art, the present invention has the following advantages:
[0027] The present invention provides a supported catalyst, wherein the supported catalyst is formed by supporting CuO and an auxiliary metal on a copper aluminum spinel (CuAl2O4), wherein the mass proportion of the CuO is 10%-30%; the mass proportion of the copper aluminum spinel is 65%-85%; and the auxiliary metal is Mg, Zn, Ce, Zr, Mo, La, Y, Cr, Ni or Co, and the mass proportion is 0-10%. The supported catalyst provided by the present invention uses the copper aluminum spinel as a carrier, and the surface is loaded with CuO and the auxiliary metal. Since the CuAl2O4 spinel has a high dispersion effect on copper oxide, the Cu particles generated by reduction show a smaller particle size. At the same time, due to the interaction between the Cu particles and the CuAl2O4 spinel carrier, and the isolation effect of the carrier, the agglomeration and growth of the copper particles are suppressed, so that the catalyst has excellent activity and long-term stability. In addition, the presence of the auxiliary metal further promotes the dispersion of copper oxide on the CuAl2O4 spinel carrier, which is beneficial to the exposure of metal copper during the reduction process of the catalyst, weakens the interaction between copper oxide and the carrier, inhibits the sintering of metal copper, and improves the catalytic stability. The catalyst can be used to synthesize a series of indole compounds such as indole, N-methylindole, 3-methylindole, N-ethylindole, and a series of indole compounds such as carbazole, N-ethylcarbazole, and N-propylcarbazole. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 The flowchart of the preparation method of the supported catalyst provided by the embodiment of the present invention is shown;
[0030] Figure 2 The SEM image of the supported catalyst provided by the embodiment of the present invention is shown;
[0031] Figure 3 The XRD spectrum of the supported catalyst provided in the embodiment of the present invention is shown;
[0032] Figure 4 The N2 adsorption-desorption curve of the supported catalyst provided in the embodiment of the present invention is shown;
[0033] Figure 5 The pore size distribution diagram of the supported catalyst provided by the embodiment of the present invention is shown;
[0034] Figure 6The figure shows the trend of the reaction yield of the supported catalyst provided in the embodiment of the present invention for synthesizing N-methylindole by the alcohol amine method as a function of the reaction time. DETAILED DESCRIPTION
[0035] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means a limitation on the present invention and its application or use. Based on the embodiments of the present invention, any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts falls within the scope of protection of the present invention. In addition, all other embodiments obtained by ordinary technicians in this field without carrying out creative work belong to the scope of protection of the present invention.
[0036] In the embodiment, no specific experimental steps or conditions are indicated, and the operation or conditions of the conventional experimental steps described in the prior art in this field can be carried out. The reagents used and other instruments that do not indicate the manufacturer are conventional reagent products that can be obtained commercially. In addition, the accompanying drawings are only schematic diagrams of the embodiments of the present invention and are not necessarily drawn to scale. The same reference numerals in the figures represent the same or similar parts, and thus their repeated description will be omitted. Some block diagrams shown in the accompanying drawings are functional entities and do not necessarily correspond to physically or logically independent entities.
[0037] Technologies, methods, and equipment known to ordinary technicians in the relevant field may not be discussed in detail, but where appropriate, the technologies, methods, and equipment should be considered as part of the description of the present invention.
[0038] In the description of the present invention, it should be understood that the use of terms such as "first" and "second" to limit components is only for the convenience of distinguishing the corresponding components. Unless otherwise stated, the above terms have no special meaning and therefore cannot be understood as limiting the scope of protection of the present invention.
[0039] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0040] Compared with the high price and complex structure of precious metal catalysts, there are many types of catalysts with copper as the main active component. However, during the preparation process, due to the low Tamman temperature of copper elements, it is easy to sinter and deactivate, which increases the difficulty of catalyst preparation and greatly reduces the service life. In view of this characteristic of copper, the present invention proposes to load CuO and auxiliary metals on copper aluminum spinel to form a new catalyst structure, and at the same time provides a preparation method of this loaded catalyst, as well as its application in the synthesis of indole, indole derivatives, carbazole and carbazole derivatives by alcoholamine method, so as to achieve high-yield catalytic alcoholamine synthesis of indole, indole derivatives and carbazole, carbazole derivatives. The specific implementation content is as follows:
[0041] In a first aspect, the present invention provides a supported catalyst, wherein the supported catalyst is formed by supporting CuO and an auxiliary metal on copper aluminum spinel, wherein the mass proportion of CuO is 10% to 30%; the mass proportion of the copper aluminum spinel is 65% to 85%; and the auxiliary metal is Mg, Zn, Ce, Zr, Mo, La, Y, Cr, Ni or Co, and the mass proportion is 0 to 10%.
[0042] The main components of the supported catalyst provided in the embodiment of the present invention are CuO and CuAl2O4 spinel, which contain no or a small amount of auxiliary metal; the presence of auxiliary metal can promote the dispersion of copper oxide on the carrier CuAl2O4 spinel and the exposure of metallic copper during reduction, weaken the interaction between copper oxide and the carrier, inhibit the sintering and growth of metallic copper, and improve the catalytic stability. When there is no auxiliary metal, as a preferred result, in the supported catalyst, the mass proportion of CuO is 17% to 27%; the mass proportion of copper aluminum spinel is 70% to 80%; when there is an auxiliary metal, in the supported catalyst, the preferred mass proportion of CuO is 18% to 25%; the mass proportion of the auxiliary metal is 0.4% to 4%; the mass proportion of copper aluminum spinel is 68% to 78%.
[0043] In the supported catalyst provided by the embodiment of the present invention, CuO is highly dispersed on the CuAl2O4 spinel. When the supported catalyst participates in the synthesis of indole, carbazole and derivatives by the alcoholamine method, the CuO is in situ reduced to an active Cu component under a H2 atmosphere, and the reduced Cu particles show a smaller particle size. In addition, due to the interaction between the Cu particles and the CuAl2O4 spinel carrier, and the isolation effect of the carrier, the migration and agglomeration rate of the Cu particles is relatively low, which can effectively delay the sintering and growth of the Cu particles, thereby improving the activity and stability of the catalyst.
[0044] In a second aspect, the present invention provides a method for preparing the supported catalyst according to the first aspect. Figure 1 The flow chart of the preparation method of the supported catalyst provided in the embodiment of the present invention is shown as follows: Figure 1 As shown, the method includes:
[0045] S1, dissolving a copper precursor, an aluminum precursor, and an auxiliary metal precursor in a solvent in a certain proportion to form a mixed system;
[0046] When this step is implemented, the precursor of copper is selected from Cu(NO3)2·3H2O; the precursor of aluminum is selected from Al(NO3)3·9H2O; the precursor of the auxiliary metal is selected from soluble salts containing Mg, Zn, Ce, Zr, Mo, La, Y, Cr, Ni or Co, which can be nitrates, sulfates, acetates, chloride salts or ammonium salts; the solvent is selected from deionized water, or an aqueous solution containing hexadecyltrimethylammonium chloride; when the solvent is selected from an aqueous solution of hexadecyltrimethylammonium chloride (CTAC), CTAC is used as a surfactant. The addition of CTAC can increase the specific surface area of the catalyst, reduce the size of the crystallites, and improve the stability of the catalyst. In this embodiment, the amount of CTAC added is determined according to the content of total metal cations in the mixed system, and the molar ratio of CTAC to total metal cations is not greater than 0.1. In addition, the concentration of total metal cations in the mixed system is between 0.25 mol / L and 2 mol / L.
[0047] In the mixed system formed by dissolving the copper precursor, aluminum precursor, and auxiliary metal precursor in a certain proportion in the solvent, the molar ratio of copper ions, aluminum ions, and auxiliary metal ions is controlled at 1:1:0 to 1:3:0.1. When the auxiliary metal precursor is not added, the content of auxiliary metal ions in the obtained mixed system is 0. At the same time, the molar ratio of copper ions to aluminum ions in the mixed system needs to be controlled at 1:1 to 1:3. This is because when aluminum is excessive (such as the molar ratio of copper ions to aluminum ions is 1:4), part of the copper element will exist in the form of Cu-O-Al intermediates after calcination, resulting in a decrease in the content of active components; when the copper content is high (such as the molar ratio of copper ions to aluminum ions is 2:1), the catalyst particle size obtained after calcination is large, resulting in an accelerated deactivation rate; in addition, the raw material copper-aluminum ratio will also affect the surface structure of the catalyst, resulting in changes in the interaction between Cu particles and the carrier.
[0048] S2, adding alkali solution to the mixed system, adjusting the pH of the system to 9-11, aging for 12 h-24 h, collecting the solid by centrifugation, washing and drying to obtain a catalyst precursor;
[0049] When this step is implemented, the alkali solution can be selected from sodium carbonate solution, sodium hydroxide solution or ammonia solution; after the pH of the mixed system is adjusted to 9-11 by the alkali solution, the metal ions in the mixed system co-precipitate in an alkaline environment to form a metal hydroxide precipitate for subsequent roasting.
[0050] S3, grinding the catalyst precursor, and then placing it in a muffle furnace, and calcining it at 600° C. to 1000° C. for 1 h to 6 h to obtain the supported catalyst;
[0051] When this step is implemented, the calcination temperature of the catalyst will affect the physical phase composition of the catalyst. At a suitable calcination temperature, the CuO particles are highly dispersed on the CuAl2O4 spinel carrier, showing a lower reduction temperature, and the Cu particles generated by reduction have a small particle size and high catalyst activity. When the calcination temperature is too high, the content of highly dispersed CuO gradually decreases, and more copper particles enter the spinel skeleton structure, gradually transforming into spinel copper ions that are difficult to reduce, and the content of active Cu components decreases. When the calcination temperature is too low, the spinel phase is not fully formed, and the CuO particles have a large particle size and poor dispersion. The calcination temperature obtained by the present invention through experimental research is between 600°C and 1000°C, and the heating rate is 2°C·min -1 ~6 ℃·min -1 The preferred calcination temperature is between 750℃ and 800℃, and the heating rate is 4℃·min -1 .
[0052] The present invention synthesizes a CuO-loaded CuAl2O4 spinel catalyst by a coprecipitation method, has a simple and easy-to-operate preparation process, mild reaction conditions, good repeatability, and has industrial-grade scale-up potential.
[0053] In a third aspect, the present invention provides an application of the supported catalyst described in the first aspect, wherein the supported catalyst is used as a catalyst for synthesizing indole, carbazole and derivatives by an alcoholamine process.
[0054] In specific implementation, the catalyst prepared by the present invention has excellent activity and long-term stability for the synthesis of indole and derivatives by the alcoholamine method. Taking the synthesis of N-methyl indole as an example, the product yield is maintained at more than 85% in the first 8 hours of the reaction, and the yield of the product N-methyl indole can still be maintained at more than 50% after 30 hours of reaction, and a high yield is obtained while achieving high stability. This is because, compared with other carriers, CuAl2O4 spinel has a high dispersion effect on copper oxide, the prepared CuO particles have good dispersibility, and the reduced Cu particles show a smaller particle size. In addition, due to the interaction between the Cu particles and the spinel carrier and the isolation effect of the carrier, the agglomeration and growth of the copper particles are suppressed, thereby improving the stability of the catalyst.
[0055] The catalyst of the present invention is universal for synthesizing indole and its derivatives by the alcoholamine method, and can be used for synthesizing indole and its derivatives, including N-methylindole, indole, and 3-methylindole, and has an excellent catalytic effect on synthesizing N-methylindole.
[0056] In some embodiments, in the reaction raw materials for synthesizing indole, carbazole and derivatives by the alcoholamine method, the molar ratio of amine to alcohol is between 3:1 and 9:1, the raw alcohol includes ethylene glycol, 1,2-propylene glycol or 1,2-cyclohexanediol, and the raw amine includes aniline or N-methylaniline; the process conditions for synthesizing indole and derivatives by the alcoholamine method include: reaction temperature, 250°C to 330°C; the reaction raw material feed space velocity is 0.1 h -1 ~2.0 h -1 The process conditions for synthesizing carbazole and its derivatives by the alcoholamine method include: reaction temperature of 280℃~380℃; feed space velocity of reaction raw materials of 0.1h -1 ~2.0 h -1 .
[0057] In order to enable those skilled in the art to more clearly understand the present invention, the supported catalyst, preparation method and application of the supported catalyst in the present invention in the synthesis of indole, carbazole and derivatives are described in detail through the following examples.
[0058] Example 1
[0059] (1) Weigh 2.42 g of copper nitrate trihydrate (Cu(NO3)2·3H2O) and 7.5 g of aluminum nitrate nonahydrate (Al(NO3)3·9H2O) and dissolve them in 40 ml of deionized water to form a mixed system (the molar ratio of copper to aluminum in the mixed system is 1:2);
[0060] Weigh 1.48 g of anhydrous sodium carbonate Na2CO3 and dissolve it in 40 ml of deionized water; weigh 2.8 g of sodium hydroxide NaOH and dissolve it in 35 ml of deionized water;
[0061] (2) Add the prepared sodium carbonate Na2CO3 and sodium hydroxide NaOH to the obtained mixed system to adjust the pH of the solution to about 10, and age it for 24 hours. Centrifuge and wash until the supernatant is neutral, and dry the obtained solid at 80 °C for 12 hours to obtain a catalyst precursor;
[0062] (3) After the dried catalyst precursor is ground evenly, it is placed in a muffle furnace and calcined at 700 °C for 5 h at a heating rate of 5 °C min -1 , a catalyst was obtained (the mass proportion of CuO was 24%, and the mass proportion of copper aluminum spinel was 76%).
[0063] Catalyst evaluation: used for the reaction of N-methylaniline and ethylene glycol to generate N-methylindole. The reaction was carried out in a fixed-bed gas-solid reactor at atmospheric pressure. 1.0 g of catalyst was weighed and loaded into the reactor for in-situ reduction. First, nitrogen was pre-flowed for 30 minutes, and then the volume ratio of hydrogen to nitrogen was 1:4. The reduction temperature was 180 °C and the time was 2 h. After the reduction was completed, the temperature was raised to 300 °C and the raw material reaction was started. The molar ratio of N-methylaniline to ethylene glycol was 5:1, and the raw material feed space velocity was 0.4 h -1 The evaluation conditions and results are shown in Table 1.
[0064] Figure 2 1 shows the SEM images of the supported catalyst provided in the embodiment of the present invention, wherein FIG. a is a SEM image of the supported catalyst at 10 μm, FIG. b is a SEM image of the supported catalyst at 2 μm, and FIG. c is a SEM image of the supported catalyst at 500 μm. Figure 2 As shown, from the SEM image at 10 μm, it can be seen that the overall particle size of the supported catalyst particles is small, and most of the particles are less than 10 μm in size. A detailed observation of the morphology of the catalyst at 2 μm revealed that the catalyst surface exhibits a flaky stacking morphology. The characteristics of the catalyst surface may indicate excellent catalytic active sites, and further at 500 nm, it can be seen that the catalyst has a rich pore structure, which provides convenient conditions for the catalytic reaction.
[0065] Figure 3 The XRD spectrum of the supported catalyst provided in the embodiment of the present invention is shown in FIG. Figure 3 As shown in the figure, the diffraction peaks at 35.5° and 37.8° correspond to the characteristic diffraction peaks of CuO, and the broad diffraction peak at 37.3° corresponds to the characteristic diffraction peak of CuAl2O4 spinel. The other diffraction peaks also belong to CuO and CuAl2O4 spinel respectively. It can be analyzed that the components of the supported catalyst are mainly highly dispersed CuO and CuAl2O4 spinel.
[0066] Figure 4 The N2 adsorption-desorption curve of the supported catalyst provided in the embodiment of the present invention is shown. Figure 4 It can be seen that the N2 adsorption-desorption isotherm is a type IV isotherm with an H3 type hysteresis loop, which indicates that most of the pores inside the CuAl2O4 spinel catalyst material are mesoporous, and the calculated BET specific surface area is about 99.7 m 2 / g, which further illustrates that the active sites created by the pores play an important role in the catalytic process.
[0067] Figure 5 The pore size distribution diagram of the supported catalyst provided in the embodiment of the present invention is shown in FIG. Figure 5As shown, the main pore size of the supported catalyst is concentrated around 20 nm.
[0068] Figure 6 The following is a graph showing the change trend of the reaction yield of the supported catalyst provided in the embodiment of the present invention for synthesizing N-methylindole by the alcoholamine method as a function of reaction time. Figure 6 As shown in the data, within the first 8 h of the reaction, the product yield of the one-step synthesis of N-methylindole from N-methylaniline and ethylene glycol was above 80%, which shows that the catalyst has excellent catalytic performance. With the extension of the reaction time, the reaction yield showed a gradually decreasing trend. After 30 h of reaction, the reaction yield was still maintained at above 50%, indicating that the catalyst has good stability in the catalytic process. The copper-aluminum spinel carrier improves the anti-sintering ability of Cu particles, and the stability is significantly improved compared with previous literature reports.
[0069] Example 2
[0070] (1) Weigh 2.42 g of copper nitrate trihydrate (Cu(NO3)2·3H2O) and 7.5 g of aluminum nitrate nonahydrate (Al(NO3)3·9H2O) and dissolve them in 40 ml of deionized water to form a mixed system (the molar ratio of copper to aluminum in the mixed system is 1:2);
[0071] Weigh 1.48 g of anhydrous sodium carbonate Na2CO3 and dissolve it in 40 ml of deionized water; weigh 2.8 g of sodium hydroxide NaOH and dissolve it in 35 ml of deionized water;
[0072] (2) To the obtained mixed system, add the prepared sodium carbonate Na2CO3 and sodium hydroxide NaOH to adjust the pH of the solution to about 10, and age it for 24 hours. Centrifuge and wash until the supernatant is neutral, and dry the obtained solid at 80 °C for 12 hours to obtain a catalyst precursor;
[0073] (3) After the dried catalyst precursor is ground evenly, it is placed in a muffle furnace and calcined at 1000 °C for 5 h at a heating rate of 5 °C min -1 , to obtain a catalyst.
[0074] Catalyst evaluation: used for the reaction of N-methylaniline and ethylene glycol to generate N-methylindole. The reaction was carried out in a fixed-bed gas-solid reactor at atmospheric pressure. 1.0 g of catalyst was weighed and loaded into the reactor for in-situ reduction. First, nitrogen was pre-flowed for 30 min, and then the volume ratio of hydrogen to nitrogen was 1:4. The reduction temperature was 180 °C and the time was 2 h. After the reduction was completed, the temperature was raised to 300 °C and the raw material reaction was started. The molar ratio of N-methylaniline to ethylene glycol was 5:1, and the raw material feed space velocity was 0.4 h -1 The evaluation conditions and results are shown in Table 1.
[0075] Example 3
[0076] (1) Weigh 2.42 g of copper nitrate trihydrate (Cu(NO3)2·3H2O) and 7.5 g of aluminum nitrate nonahydrate (Al(NO3)3·9H2O) and dissolve them in 40 ml of deionized water to form a mixed system (the molar ratio of copper to aluminum in the mixed system is 1:2);
[0077] Weigh 1.48 g of anhydrous sodium carbonate Na2CO3 and dissolve it in 40 ml of deionized water; weigh 2.8 g of sodium hydroxide NaOH and dissolve it in 35 ml of deionized water;
[0078] (2) To the obtained mixed system, add the prepared sodium carbonate Na2CO3 and sodium hydroxide NaOH to adjust the pH of the solution to about 10, and age it for 24 hours. Centrifuge and wash until the supernatant is neutral, and dry the obtained solid at 80 °C for 12 hours to obtain a catalyst precursor;
[0079] (3) The dried catalyst precursor was ground evenly and then placed in a muffle furnace for calcination at 600 °C for 5 h at a heating rate of 5 °C min -1 , to obtain a catalyst.
[0080] Catalyst evaluation: used for the reaction of N-methylaniline and ethylene glycol to generate N-methylindole. The reaction was carried out in a fixed-bed gas-solid reactor at atmospheric pressure. 1.0 g of catalyst was weighed and loaded into the reactor for in-situ reduction. First, nitrogen was pre-flowed for 30 min, and then the volume ratio of hydrogen to nitrogen was 1:4. The reduction temperature was 180 °C and the time was 2 h. After the reduction was completed, the temperature was raised to 300 °C and the raw material reaction was started. The molar ratio of N-methylaniline to ethylene glycol was 5:1, and the raw material feed space velocity was 0.4 h -1 The evaluation conditions and results are shown in Table 1.
[0081] Example 4
[0082] (1) Weigh 2.42 g of copper nitrate trihydrate (Cu(NO3)2·3H2O) and 11.25 g of aluminum nitrate nonahydrate (Al(NO3)3·9H2O) and dissolve them in 40 ml of deionized water to form a mixed system (the molar ratio of copper to aluminum in the mixed system is 1:3);
[0083] Weigh 1.48 g of anhydrous sodium carbonate Na2CO3 and dissolve it in 40 ml of deionized water; weigh 2.8 g of sodium hydroxide NaOH and dissolve it in 35 ml of deionized water;
[0084] (2) To the obtained mixed system, add the prepared sodium carbonate Na2CO3 and sodium hydroxide NaOH to adjust the pH of the solution to about 10, and age it for 24 hours. Centrifuge and wash until the supernatant is neutral, and dry the obtained solid at 80 °C for 12 hours to obtain a catalyst precursor;
[0085] (3) The dried catalyst precursor was ground evenly and then placed in a muffle furnace for calcination at 700 °C for 5 h at a heating rate of 5 °C min -1 , a catalyst was obtained (the mass proportion of CuO was 15%, and the mass proportion of copper aluminum spinel was 85%).
[0086] Catalyst evaluation: used for the reaction of N-methylaniline and ethylene glycol to generate N-methylindole. The reaction was carried out in a fixed-bed gas-solid reactor at atmospheric pressure. 1.0 g of catalyst was weighed and loaded into the reactor for in-situ reduction. First, nitrogen was pre-flowed for 30 min, and then the volume ratio of hydrogen to nitrogen was 1:4. The reduction temperature was 180 °C and the time was 2 h. After the reduction was completed, the temperature was raised to 300 °C and the raw materials were introduced for reaction. The molar ratio of N-methylaniline to ethylene glycol was 5:1, and the raw material feed space velocity was 0.4 h -1 The evaluation conditions and results are shown in Table 1.
[0087] Example 5
[0088] (1) Weigh 2.42 g of copper nitrate trihydrate (Cu(NO3)2·3H2O) and 3.75 g of aluminum nitrate nonahydrate (Al(NO3)3·9H2O) and dissolve them in 40 ml of deionized water to form a mixed system (the molar ratio of copper to aluminum in the mixed system is 1:1);
[0089] Weigh 1.48 g of anhydrous sodium carbonate Na2CO3 and dissolve it in 40 ml of deionized water; weigh 2.8 g of sodium hydroxide NaOH and dissolve it in 35 ml of deionized water;
[0090] (2) Add the prepared sodium carbonate Na2CO3 and sodium hydroxide NaOH to the mixed system to adjust the pH of the solution to about 10, and age it for 24 hours. Centrifuge and wash until the supernatant is neutral, and dry the obtained solid at 80 °C for 12 hours to obtain a catalyst precursor;
[0091] (3) The dried catalyst precursor was ground evenly and then placed in a muffle furnace for calcination at 700 °C for 5 h at a heating rate of 5 °C min -1 , a catalyst was obtained (the mass proportion of CuO was 30%, and the mass proportion of copper aluminum spinel was 70%).
[0092] Catalyst evaluation: used for the reaction of N-methylaniline and ethylene glycol to generate N-methylindole. The reaction was carried out in a fixed-bed gas-solid reactor at atmospheric pressure. 1.0 g of catalyst was weighed and loaded into the reactor for in-situ reduction. First, nitrogen was pre-flowed for 30 min, and then the volume ratio of hydrogen to nitrogen was 1:4. The reduction temperature was 180 °C and the time was 2 h. After the reduction was completed, the temperature was raised to 300 °C and the raw material reaction was started. The molar ratio of N-methylaniline to ethylene glycol was 5:1, and the raw material feed space velocity was 0.4 h -1 The evaluation conditions and results are shown in Table 1.
[0093] Example 6
[0094] (1) Weigh 0.64 g of hexadecyltrimethylammonium chloride (CTAC) and add it to 40 mL of deionized water, stir to dissolve it completely, then weigh 2.42 g of copper nitrate trihydrate (Cu(NO3)2·3H2O) and 7.5 g of aluminum nitrate nonahydrate (Al(NO3)3·9H2O) and add them to the above solution and stir to dissolve them completely to form a mixed system (in the mixed system, the molar ratio of copper to aluminum is 1:2; the molar ratio of CTAC to total metal ions is 0.067);
[0095] Weigh 1.48 g of anhydrous sodium carbonate Na2CO3 and dissolve it in 40 ml of deionized water; weigh 2.8 g of sodium hydroxide NaOH and dissolve it in 35 ml of deionized water;
[0096] (2) Add the prepared sodium carbonate Na2CO3 and sodium hydroxide NaOH to the mixed system to adjust the pH of the solution to about 10, and age it for 24 hours. Centrifuge and wash until the supernatant is neutral, and dry the obtained solid at 80 °C for 12 hours to obtain a catalyst precursor;
[0097] (3) The dried catalyst precursor was ground evenly and then placed in a muffle furnace for calcination at 700 °C for 5 h at a heating rate of 5 °C min -1 , a catalyst was obtained (the mass proportion of CuO was 23% and the mass proportion of copper aluminum spinel was 77%).
[0098] Catalyst evaluation: used for the reaction of N-methylaniline and ethylene glycol to generate N-methylindole. The reaction was carried out in a fixed-bed gas-solid reactor at atmospheric pressure. 1.0 g of catalyst was weighed and loaded into the reactor for in-situ reduction. First, nitrogen was pre-flowed for 30 min, and then the volume ratio of hydrogen to nitrogen was 1:4. The reduction temperature was 180 °C and the time was 2 h. After the reduction was completed, the temperature was raised to 300 °C and the raw material reaction was started. The molar ratio of N-methylaniline to ethylene glycol was 5:1, and the raw material feed space velocity was 0.4 h -1 The evaluation conditions and results are shown in Table 1.
[0099] Example 7
[0100] (1) Weigh 0.96 g of hexadecyltrimethylammonium chloride (CTAC) and add it to 40 mL of deionized water, stir to dissolve it completely, then weigh 2.42 g of copper nitrate trihydrate (Cu(NO3)2·3H2O) and 7.5 g of aluminum nitrate nonahydrate (Al(NO3)3·9H2O) and add them to the above solution and stir to dissolve them completely to form a mixed system (in the mixed system, the molar ratio of copper to aluminum is 1:2, and the molar ratio of CTAC to total metal ions is 0.1);
[0101] Weigh 1.48 g of anhydrous sodium carbonate Na2CO3 and dissolve it in 40 ml of deionized water; weigh 2.8 g of sodium hydroxide NaOH and dissolve it in 35 ml of deionized water;
[0102] (2) Add the prepared sodium carbonate Na2CO3 and sodium hydroxide NaOH to the mixed system to adjust the pH of the solution to about 10, and age it for 24 hours. Centrifuge and wash until the supernatant is neutral, and dry the obtained solid at 80 °C for 12 hours to obtain a catalyst precursor;
[0103] (3) The dried catalyst precursor was ground evenly and then placed in a muffle furnace for calcination at 700 °C for 5 h at a heating rate of 5 °C min -1 , to obtain a catalyst.
[0104] Catalyst evaluation: used for the reaction of N-methylaniline and ethylene glycol to generate N-methylindole. The reaction was carried out in a fixed-bed gas-solid reactor at atmospheric pressure. 1.0 g of catalyst was weighed and loaded into the reactor for in-situ reduction. First, nitrogen was pre-flowed for 30 min, and then the volume ratio of hydrogen to nitrogen was 1:4. The reduction temperature was 180 °C and the time was 2 h. After the reduction was completed, the temperature was raised to 300 °C and the raw material reaction was started. The molar ratio of N-methylaniline to ethylene glycol was 5:1, and the raw material feed space velocity was 0.4 h -1 The evaluation conditions and results are shown in Table 1.
[0105] Example 8
[0106] (1) Weigh 0.32 g of hexadecyltrimethylammonium chloride (CTAC) and add it to 40 mL of deionized water, stir to dissolve it completely, then weigh 2.4 g of copper nitrate trihydrate (Cu(NO3)2·3H2O) and 7.5 g of aluminum nitrate nonahydrate (Al(NO3)3·9H2O) and add them to the above solution and stir to dissolve completely to form a mixed system (in the mixed system, the molar ratio of copper to aluminum is 1:2, and the molar ratio of CTAC to total metal ions is 0.033);
[0107] Weigh 1.48 g of anhydrous sodium carbonate Na2CO3 and dissolve it in 40 ml of deionized water; weigh 2.8 g of sodium hydroxide NaOH and dissolve it in 35 ml of deionized water;
[0108] (2) Add the prepared sodium carbonate Na2CO3 and sodium hydroxide NaOH to the mixed system to adjust the pH of the solution to about 10, and age it for 24 hours. Centrifuge and wash until the supernatant is neutral, and dry the obtained solid at 80 °C for 12 hours to obtain a catalyst precursor;
[0109] (3) The dried catalyst precursor was ground evenly and then placed in a muffle furnace for calcination at 700 °C for 5 h at a heating rate of 5 °C min -1 , to obtain a catalyst.
[0110] Catalyst evaluation: used for the reaction of N-methylaniline and ethylene glycol to generate N-methylindole. The reaction was carried out in a fixed-bed gas-solid reactor at atmospheric pressure. 1.0 g of catalyst was weighed and loaded into the reactor for in-situ reduction. First, nitrogen was pre-flowed for 30 min, and then the volume ratio of hydrogen to nitrogen was 1:4. The reduction temperature was 180 °C and the time was 2 h. After the reduction was completed, the temperature was raised to 300 °C and the raw material reaction was started. The molar ratio of N-methylaniline to ethylene glycol was 5:1, and the raw material feed space velocity was 0.4 h -1 The evaluation conditions and results are shown in Table 1.
[0111] Example 9
[0112] (1) Weigh 2.42 g of copper nitrate trihydrate (Cu(NO3)2·3H2O), 7.5 g of aluminum nitrate nonahydrate (Al(NO3)3·9H2O) and 0.13 g of magnesium nitrate hexahydrate (Mg(NO3)2·6H2O) and dissolve them in 40 ml of deionized water to form a mixed system (in the mixed system, the molar ratio of copper to aluminum is 1:2, and the molar ratio of magnesium ion to copper ion is 0.05);
[0113] Weigh 1.48 g of anhydrous sodium carbonate Na2CO3 and dissolve it in 40 ml of deionized water; weigh 2.8 g of sodium hydroxide NaOH and dissolve it in 35 ml of deionized water;
[0114] (2) Add the prepared sodium carbonate Na2CO3 and sodium hydroxide NaOH to the mixed system to adjust the pH of the solution to about 10, and age it for 24 hours. Centrifuge and wash until the supernatant is neutral, and dry the obtained solid at 80 °C for 12 hours to obtain a catalyst precursor;
[0115] (3) The dried catalyst precursor was ground evenly and then placed in a muffle furnace for calcination at 700 °C for 5 h at a heating rate of 5 °C min -1, a catalyst was obtained (the mass proportion of CuO was 23%, the mass proportion of copper aluminum spinel was 75%, and the mass proportion of auxiliary metal was 2%).
[0116] Catalyst evaluation: used for the reaction of N-methylaniline and ethylene glycol to generate N-methylindole. The reaction was carried out in a fixed-bed gas-solid reactor at atmospheric pressure. 1.0 g of catalyst was weighed and loaded into the reactor for in-situ reduction. First, nitrogen was pre-flowed for 30 min, and then the volume ratio of hydrogen to nitrogen was 1:4. The reduction temperature was 180 °C and the time was 2 h. After the reduction was completed, the temperature was raised to 300 °C and the raw material reaction was started. The molar ratio of N-methylaniline to ethylene glycol was 5:1, and the raw material feed space velocity was 0.4 h -1 The evaluation conditions and results are shown in Table 1.
[0117] Example 10
[0118] (1) Weigh 2.42 g of copper nitrate trihydrate (Cu(NO3)2·3H2O), 7.5 g of aluminum nitrate nonahydrate (Al(NO3)3·9H2O) and 0.25 g of magnesium nitrate hexahydrate (Mg(NO3)2·6H2O) and dissolve them in 40 ml of deionized water to form a mixed system (in the mixed system, the molar ratio of copper to aluminum is 1:2, and the molar ratio of magnesium ion to copper ion is 0.1);
[0119] Weigh 1.48 g of anhydrous sodium carbonate Na2CO3 and dissolve it in 40 ml of deionized water; weigh 2.8 g of sodium hydroxide NaOH and dissolve it in 35 ml of deionized water;
[0120] (2) Add the prepared sodium carbonate Na2CO3 and sodium hydroxide NaOH to the mixed system to adjust the pH of the solution to about 10, and age it for 24 hours. Centrifuge and wash until the supernatant is neutral, and dry the obtained solid at 80 °C for 12 hours to obtain a catalyst precursor;
[0121] (3) The dried catalyst precursor was ground evenly and then placed in a muffle furnace for calcination at 700 °C for 5 h at a heating rate of 5 °C min -1 , a catalyst was obtained (the mass proportion of CuO was 22%, the mass proportion of copper aluminum spinel was 75%, and the mass proportion of auxiliary metal was 3%).
[0122] Catalyst evaluation: used for the reaction of N-methylaniline and ethylene glycol to generate N-methylindole. The reaction was carried out in a fixed-bed gas-solid reactor at atmospheric pressure. 1.0 g of catalyst was weighed and loaded into the reactor for in-situ reduction. First, nitrogen was pre-flowed for 30 min, and then the volume ratio of hydrogen to nitrogen was 1:4. The reduction temperature was 180 °C and the time was 2 h. After the reduction was completed, the temperature was raised to 300 °C and the raw material reaction was started. The molar ratio of N-methylaniline to ethylene glycol was 5:1, and the raw material feed space velocity was 0.4 h -1 The evaluation conditions and results are shown in Table 1.
[0123] Embodiment 11
[0124] (1) Weigh 2.42 g of copper nitrate trihydrate (Cu(NO3)2·3H2O), 7.5 g of aluminum nitrate nonahydrate (Al(NO3)3·9H2O) and 0.3 g of zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and dissolve them in 40 ml of deionized water to form a mixed system (in the mixed system, the molar ratio of copper to aluminum is 1:2, and the molar ratio of zinc ion to copper ion is 0.1);
[0125] Weigh 1.48 g of anhydrous sodium carbonate Na2CO3 and dissolve it in 40 ml of deionized water; weigh 2.8 g of sodium hydroxide NaOH and dissolve it in 35 ml of deionized water;
[0126] (2) Add the prepared sodium carbonate Na2CO3 and sodium hydroxide NaOH to the mixed system to adjust the pH of the solution to about 10, and age it for 24 hours. Centrifuge and wash until the supernatant is neutral, and dry the obtained solid at 80 °C for 12 hours to obtain a catalyst precursor;
[0127] (3) The dried catalyst precursor was ground evenly and then placed in a muffle furnace for calcination at 700 °C for 5 h at a heating rate of 5 °C min -1 , a catalyst was obtained (the mass proportion of CuO was 22%, the mass proportion of copper aluminum spinel was 74%, and the mass proportion of auxiliary metal was 4%).
[0128] Catalyst evaluation: used for the reaction of N-methylaniline and ethylene glycol to generate N-methylindole. The reaction was carried out in a fixed-bed gas-solid reactor at atmospheric pressure. 1.0 g of catalyst was weighed and loaded into the reactor for in-situ reduction. First, nitrogen was pre-flowed for 30 min, and then the volume ratio of hydrogen to nitrogen was 1:4. The reduction temperature was 180 °C and the time was 2 h. After the reduction was completed, the temperature was raised to 300 °C and the raw material reaction was started. The molar ratio of N-methylaniline to ethylene glycol was 5:1, and the raw material feed space velocity was 0.4 h -1 The evaluation conditions and results are shown in Table 1.
[0129] Example 12
[0130] (1) Weigh 2.42 g of copper nitrate trihydrate (Cu(NO3)2·3H2O), 7.5 g of aluminum nitrate nonahydrate (Al(NO3)3·9H2O) and 0.29 g of nickel nitrate hexahydrate (Ni(NO3)2·6H2O) and dissolve them in 40 ml of deionized water to form a mixed system (in the mixed system, the molar ratio of copper to aluminum is 1:2, and the molar ratio of nickel ion to copper ion is 0.1);
[0131] Weigh 1.48 g of anhydrous sodium carbonate Na2CO3 and dissolve it in 40 ml of deionized water; weigh 2.8 g of sodium hydroxide NaOH and dissolve it in 35 ml of deionized water;
[0132] (2) Add the prepared sodium carbonate Na2CO3 and sodium hydroxide NaOH to the mixed system to adjust the pH of the solution to about 10, and age it for 24 hours. Centrifuge and wash until the supernatant is neutral, and dry the obtained solid at 80 °C for 12 hours to obtain a catalyst precursor;
[0133] (3) The dried catalyst precursor was ground evenly and then placed in a muffle furnace for calcination at 700 °C for 5 h at a heating rate of 5 °C min -1 , a catalyst was obtained (the mass proportion of CuO was 22%, the mass proportion of copper aluminum spinel was 74%, and the mass proportion of auxiliary metal was 4%).
[0134] Catalyst evaluation: used for the reaction of N-methylaniline and ethylene glycol to generate N-methylindole. The reaction was carried out in a fixed-bed gas-solid reactor at atmospheric pressure. 1.0 g of catalyst was weighed and loaded into the reactor for in-situ reduction. First, nitrogen was pre-flowed for 30 min, and then the volume ratio of hydrogen to nitrogen was 1:4. The reduction temperature was 180 °C and the time was 2 h. After the reduction was completed, the temperature was raised to 300 °C and the raw material reaction was started. The molar ratio of N-methylaniline to ethylene glycol was 5:1, and the raw material feed space velocity was 0.4 h -1 The evaluation conditions and results are shown in Table 1.
[0135] Example 13
[0136] (1) Weigh 2.42 g of copper nitrate trihydrate (Cu(NO3)2·3H2O), 7.5 g of aluminum nitrate nonahydrate (Al(NO3)3·9H2O) and 0.434 g of cerium nitrate hexahydrate (Ce(NO3)3·6H2O) and dissolve them in 40 ml of deionized water to form a mixed system (in the mixed system, the molar ratio of copper to aluminum is 1:2, and the molar ratio of cerium ion to copper ion is 0.1);
[0137] Weigh 1.48 g of anhydrous sodium carbonate Na2CO3 and dissolve it in 40 ml of deionized water; weigh 2.8 g of sodium hydroxide NaOH and dissolve it in 35 ml of deionized water;
[0138] (2) Add the prepared sodium carbonate Na2CO3 and sodium hydroxide NaOH to the mixed system to adjust the pH of the solution to about 10, and age it for 24 hours. Centrifuge and wash until the supernatant is neutral, and dry the obtained solid at 80 °C for 12 hours to obtain a catalyst precursor;
[0139] (3) The dried catalyst precursor was ground evenly and then placed in a muffle furnace for calcination at 700 °C for 5 h at a heating rate of 5 °C min -1 , a catalyst was obtained (the mass proportion of CuO was 23%, the mass proportion of copper aluminum spinel was 70%, and the mass proportion of auxiliary metal was 7%).
[0140] Catalyst evaluation: used for the reaction of N-methylaniline and ethylene glycol to generate N-methylindole. The reaction was carried out in a fixed-bed gas-solid reactor at atmospheric pressure. 1.0 g of catalyst was weighed and loaded into the reactor for in-situ reduction. First, nitrogen was pre-flowed for 30 min, and then the volume ratio of hydrogen to nitrogen was 1:4. The reduction temperature was 180 °C and the time was 2 h. After the reduction was completed, the temperature was raised to 300 °C and the raw material reaction was started. The molar ratio of N-methylaniline to ethylene glycol was 5:1, and the raw material feed space velocity was 0.4 h -1 The evaluation conditions and results are shown in Table 1.
[0141] Embodiment 14
[0142] (1) Weigh 2.42 g of copper nitrate trihydrate (Cu(NO3)2·3H2O), 7.5 g of aluminum nitrate nonahydrate (Al(NO3)3·9H2O) and 0.429 g of zirconium nitrate pentahydrate (Zr(NO3)4·5H2O) and dissolve them in 40 ml of deionized water to form a mixed system (in the mixed system, the molar ratio of copper to aluminum is 1:2, and the molar ratio of zirconium ion to copper ion is 0.1);
[0143] Weigh 1.48 g of anhydrous sodium carbonate Na2CO3 and dissolve it in 40 ml of deionized water; weigh 2.8 g of sodium hydroxide NaOH and dissolve it in 35 ml of deionized water;
[0144] (2) Add the prepared sodium carbonate Na2CO3 and sodium hydroxide NaOH to the mixed system to adjust the pH of the solution to about 10, and age it for 24 hours. Centrifuge and wash until the supernatant is neutral, and dry the obtained solid at 80 °C for 12 hours to obtain a catalyst precursor;
[0145] (3) The dried catalyst precursor was ground evenly and then placed in a muffle furnace for calcination at 700 °C for 5 h at a heating rate of 5 °C min -1 , a catalyst was obtained (the mass proportion of CuO was 23%, the mass proportion of copper aluminum spinel was 73%, and the mass proportion of auxiliary metal was 4%).
[0146] Catalyst evaluation: used for the reaction of N-methylaniline and ethylene glycol to generate N-methylindole. The reaction was carried out in a fixed-bed gas-solid reactor at atmospheric pressure. 1.0 g of catalyst was weighed and loaded into the reactor for in-situ reduction. First, nitrogen was pre-flowed for 30 min, and then the volume ratio of hydrogen to nitrogen was 1:4. The reduction temperature was 180 °C and the time was 2 h. After the reduction was completed, the temperature was raised to 300 °C and the raw material reaction was started. The molar ratio of N-methylaniline to ethylene glycol was 5:1, and the raw material feed space velocity was 0.4 h -1 The evaluation conditions and results are shown in Table 1.
[0147] Embodiment 15
[0148] (1) Weigh 2.42 g of copper nitrate trihydrate (Cu(NO3)2·3H2O), 7.5 g of aluminum nitrate nonahydrate (Al(NO3)3·9H2O), and 0.383 g of yttrium nitrate hexahydrate (Y(NO3)3·6H2O) and dissolve them in 40 ml of deionized water to form a mixed system (in the mixed system, the molar ratio of copper to aluminum is 1:2, and the molar ratio of yttrium ion to copper ion is 0.1);
[0149] Weigh 1.48 g of anhydrous sodium carbonate Na2CO3 and dissolve it in 40 ml of deionized water; weigh 2.8 g of sodium hydroxide NaOH and dissolve it in 35 ml of deionized water;
[0150] (2) Add the prepared sodium carbonate Na2CO3 and sodium hydroxide NaOH to the mixed system to adjust the pH of the solution to about 10, and age it for 24 hours. Centrifuge and wash until the supernatant is neutral, and dry the obtained solid at 80 °C for 12 hours to obtain a catalyst precursor;
[0151] (3) The dried catalyst precursor was ground evenly and then placed in a muffle furnace for calcination at 700 °C for 5 h at a heating rate of 5 °C min -1 , a catalyst was obtained (the mass proportion of CuO was 22%, the mass proportion of copper aluminum spinel was 74%, and the mass proportion of auxiliary metal was 4%).
[0152] Catalyst evaluation: used for the reaction of N-methylaniline and ethylene glycol to generate N-methylindole. The reaction was carried out in a fixed-bed gas-solid reactor at atmospheric pressure. 1.0 g of catalyst was weighed and loaded into the reactor for in-situ reduction. First, nitrogen was pre-flowed for 30 min, and then the volume ratio of hydrogen to nitrogen was 1:4. The reduction temperature was 180 °C and the time was 2 h. After the reduction was completed, the temperature was raised to 300 °C and the raw material reaction was started. The molar ratio of N-methylaniline to ethylene glycol was 5:1, and the raw material feed space velocity was 0.4 h -1 The evaluation conditions and results are shown in Table 1.
[0153] Example 16
[0154] (1) Weigh 2.42 g of copper nitrate trihydrate (Cu(NO3)2·3H2O), 7.5 g of aluminum nitrate nonahydrate (Al(NO3)3·9H2O) and 0.433 g of lanthanum nitrate hexahydrate (La(NO3)3·6H2O) and dissolve them in 40 ml of deionized water to form a mixed system (in the mixed system, the molar ratio of copper to aluminum is 1:2, and the molar ratio of lanthanum ion to copper ion is 0.1);
[0155] Weigh 1.48 g of anhydrous sodium carbonate Na2CO3 and dissolve it in 40 ml of deionized water; weigh 2.8 g of sodium hydroxide NaOH and dissolve it in 35 ml of deionized water;
[0156] (2) Add the prepared sodium carbonate Na2CO3 and sodium hydroxide NaOH to the mixed system to adjust the pH of the solution to about 10, and age it for 24 hours. Centrifuge and wash until the supernatant is neutral, and dry the obtained solid at 80 °C for 12 hours to obtain a catalyst precursor;
[0157] (3) The dried catalyst precursor was ground evenly and then placed in a muffle furnace for calcination at 700 °C for 5 h at a heating rate of 5 °C min -1 , a catalyst was obtained (the mass proportion of CuO was 23%, the mass proportion of copper aluminum spinel was 70%, and the mass proportion of auxiliary metal was 7%).
[0158] Catalyst evaluation: used for the reaction of N-methylaniline and ethylene glycol to generate N-methylindole. The reaction was carried out in a fixed-bed gas-solid reactor at atmospheric pressure. 1.0 g of catalyst was weighed and loaded into the reactor for in-situ reduction. First, nitrogen was pre-flowed for 30 min, and then the volume ratio of hydrogen to nitrogen was 1:4. The reduction temperature was 180 °C and the time was 2 h. After the reduction was completed, the temperature was raised to 300 °C and the raw material reaction was started. The molar ratio of N-methylaniline to ethylene glycol was 5:1, and the raw material feed space velocity was 0.4 h -1 The evaluation conditions and results are shown in Table 1.
[0159] Embodiment 17
[0160] (1) Weigh 2.42 g of copper nitrate trihydrate (Cu(NO3)2·3H2O), 7.5 g of aluminum nitrate nonahydrate (Al(NO3)3·9H2O) and 0.176 g of ammonium molybdate tetrahydrate ((NH4)6Mo7O 24 ·4H2O) were mixed and dissolved in 40 ml of deionized water to form a mixed system (in the mixed system, the molar ratio of copper to aluminum was 1:2, and the molar ratio of molybdenum to copper was 0.1);
[0161] Weigh 1.48 g of anhydrous sodium carbonate Na2CO3 and dissolve it in 40 ml of deionized water; weigh 2.8 g of sodium hydroxide NaOH and dissolve it in 35 ml of deionized water;
[0162] (2) Add the prepared sodium carbonate Na2CO3 and sodium hydroxide NaOH to the mixed system to adjust the pH of the solution to about 10, and age it for 24 hours. Centrifuge and wash until the supernatant is neutral, and dry the obtained solid at 80 °C for 12 hours to obtain a catalyst precursor;
[0163] (3) The dried catalyst precursor was ground evenly and then placed in a muffle furnace for calcination at 700 °C for 5 h at a heating rate of 5 °C min -1 , a catalyst was obtained (the mass proportion of CuO was 22%, the mass proportion of copper aluminum spinel was 73%, and the mass proportion of auxiliary metal was 5%).
[0164] Catalyst evaluation: used for the reaction of N-methylaniline and ethylene glycol to generate N-methylindole. The reaction was carried out in a fixed-bed gas-solid reactor at atmospheric pressure. 1.0 g of catalyst was weighed and loaded into the reactor for in-situ reduction. First, nitrogen was pre-flowed for 30 min, and then the volume ratio of hydrogen to nitrogen was 1:4. The reduction temperature was 180 °C and the time was 2 h. After the reduction was completed, the temperature was raised to 300 °C and the raw material reaction was started. The molar ratio of N-methylaniline to ethylene glycol was 5:1, and the raw material feed space velocity was 0.4 h -1 The evaluation conditions and results are shown in Table 1.
[0165] Embodiment 18
[0166] (1) Weigh 2.42 g of copper nitrate trihydrate (Cu(NO3)2·3H2O), 7.5 g of aluminum nitrate nonahydrate (Al(NO3)3·9H2O) and 0.4 g of chromium nitrate nonahydrate (Cr(NO3)3·9H2O) and dissolve them in 40 ml of deionized water to form a mixed system (in the mixed system, the molar ratio of copper to aluminum is 1:2, and the molar ratio of chromium to copper is 0.1);
[0167] Weigh 1.48 g of anhydrous sodium carbonate Na2CO3 and dissolve it in 40 ml of deionized water; weigh 2.8 g of sodium hydroxide NaOH and dissolve it in 35 ml of deionized water;
[0168] (2) Add the prepared sodium carbonate Na2CO3 and sodium hydroxide NaOH to the mixed system to adjust the pH of the solution to about 10, and age it for 24 hours. Centrifuge and wash until the supernatant is neutral, and dry the obtained solid at 80 °C for 12 hours to obtain a catalyst precursor;
[0169] (3) The dried catalyst precursor was ground evenly and then placed in a muffle furnace for calcination at 700 °C for 5 h at a heating rate of 5 °C min -1 , a catalyst was obtained (the mass proportion of CuO was 25%, the mass proportion of copper aluminum spinel was 73%, and the mass proportion of auxiliary metal was 2%).
[0170] Catalyst evaluation: used for the reaction of N-methylaniline and ethylene glycol to generate N-methylindole. The reaction was carried out in a fixed-bed gas-solid reactor at atmospheric pressure. 1.0 g of catalyst was weighed and loaded into the reactor for in-situ reduction. First, nitrogen was pre-flowed for 30 min, and then the volume ratio of hydrogen to nitrogen was 1:4. The reduction temperature was 180 °C and the time was 2 h. After the reduction was completed, the temperature was raised to 300 °C and the raw material reaction was started. The molar ratio of N-methylaniline to ethylene glycol was 5:1, and the raw material feed space velocity was 0.4 h -1 The evaluation conditions and results are shown in Table 1.
[0171] Embodiment 19
[0172] (1) Weigh 0.66 g of hexadecyltrimethylammonium chloride (CTAC) and add it to 40 mL of deionized water, stir to dissolve it completely, then weigh 2.42 g of copper nitrate trihydrate (Cu(NO3)2·3H2O), 7.5 g of aluminum nitrate nonahydrate (Al(NO3)3·9H2O) and 0.25 g of magnesium nitrate hexahydrate (Mg(NO3)2·6H2O) and add them to the above solution and stir to dissolve them completely to form a mixed system (in the mixed system, the molar ratio of copper to aluminum is 1:2, and the molar ratio of magnesium ion to copper ion is 0.1);
[0173] Weigh 1.48 g of anhydrous sodium carbonate Na2CO3 and dissolve it in 40 ml of deionized water; weigh 2.8 g of sodium hydroxide NaOH and dissolve it in 35 ml of deionized water;
[0174] (2) Add the prepared sodium carbonate Na2CO3 and sodium hydroxide NaOH to the mixed system to adjust the pH of the solution to about 10, and age it for 24 hours. Centrifuge and wash until the supernatant is neutral, and dry the obtained solid at 80 °C for 12 hours to obtain a catalyst precursor;
[0175] (3) The dried catalyst precursor was ground evenly and then placed in a muffle furnace for calcination at 700 °C for 5 h at a heating rate of 5 °C min -1 , to obtain a catalyst.
[0176] Catalyst evaluation: used for the reaction of N-methylaniline and ethylene glycol to generate N-methylindole. The reaction was carried out in a fixed-bed gas-solid reactor at atmospheric pressure. 1.0 g of catalyst was weighed and loaded into the reactor for in-situ reduction. First, nitrogen was pre-flowed for 30 min, and then the volume ratio of hydrogen to nitrogen was 1:4. The reduction temperature was 180 °C and the time was 2 h. After the reduction was completed, the temperature was raised to 300 °C and the raw material reaction was started. The molar ratio of N-methylaniline to ethylene glycol was 5:1, and the raw material feed space velocity was 0.4 h -1 The evaluation conditions and results are shown in Table 1.
[0177] Embodiment 20
[0178] The catalyst preparation process is the same as that in Example 18.
[0179] Catalyst evaluation: used for the reaction of aniline and ethylene glycol to generate indole. The reaction was carried out in a fixed-bed gas-solid reactor at normal pressure. The catalyst was obtained by the same synthesis method as in Example 18. 1.0 g was weighed and loaded into the reactor for in-situ reduction. First, nitrogen was pre-flowed for 30 min, and then the volume ratio of hydrogen to nitrogen was 1:4. The reduction temperature was 180 ° C and the time was 2 h. After the reduction was completed, the temperature was raised to 300 ° C, and the raw material reaction was started. The molar ratio of aniline to ethylene glycol was 5:1, and the raw material feed space velocity was 0.4 h -1 The evaluation conditions and results are shown in Table 1.
[0180] Embodiment 21
[0181] The catalyst preparation process is the same as that in Example 18.
[0182] Catalyst evaluation: used for the reaction of aniline and 1,2-propylene glycol to generate 3-methylindole. The reaction was carried out in a fixed-bed gas-solid reaction apparatus at normal pressure. The catalyst was obtained by the same synthesis method as in Example 18. 1.0 g was weighed and loaded into the reactor for in-situ reduction. First, nitrogen was pre-flowed for 30 min, and then the volume ratio of hydrogen to nitrogen was 1:4. The reduction temperature was 180°C and the time was 2 h. After the reduction was completed, the temperature was raised to 300°C and the raw materials were introduced for reaction. The molar ratio of aniline to 1,2-propylene glycol was 5:1 and the raw material feed space velocity was 0.4 h -1 The evaluation conditions and results are shown in Table 1.
[0183] Embodiment 22
[0184] The catalyst preparation process is the same as that in Example 18.
[0185] Catalyst evaluation: used for the reaction of aniline and 1,2-cyclohexanediol to generate carbazole. The reaction was carried out in a fixed-bed gas-solid reaction apparatus at normal pressure. The catalyst was obtained by the same synthesis method as in Example 18. 1.0 g was weighed and loaded into the reactor for in-situ reduction. First, nitrogen was pre-flowed for 30 min, and then the volume ratio of hydrogen to nitrogen was 1:4. The reduction temperature was 180 °C and the time was 2 h. After the reduction was completed, the temperature was raised to 300 °C and the raw material reaction was started. The molar ratio of aniline to 1,2-cyclohexanediol was 7:1 and the raw material feed space velocity was 0.4 h -1 The evaluation conditions and results are shown in Table 1.
[0186] Embodiment 23
[0187] The catalyst preparation process is the same as that in Example 18.
[0188] Catalyst evaluation: used for the reaction of aniline and 1,2-cyclohexanediol to generate carbazole. The reaction was carried out in a fixed-bed gas-solid reaction apparatus at normal pressure. The catalyst was obtained by the same synthesis method as in Example 18. 1.0 g was weighed and loaded into the reactor for in-situ reduction. First, nitrogen was pre-flowed for 30 min, and then the volume ratio of hydrogen to nitrogen was 1:4. The reduction temperature was 180 ° C and the time was 2 h. After the reduction was completed, the temperature was raised to 350 ° C and the raw material reaction was started. The molar ratio of aniline to 1,2-cyclohexanediol was 7:1, and the raw material feed space velocity was 0.4 h -1 The evaluation conditions and results are shown in Table 1.
[0189] Embodiment 24
[0190] The catalyst preparation process is the same as that in Example 18.
[0191] Catalyst evaluation: used for the reaction of N-ethylaniline and 1,2-cyclohexanediol to generate N-ethylcarbazole. The reaction was carried out in a fixed-bed gas-solid reaction device at normal pressure. The catalyst was obtained by the same synthesis method as in Example 18. 1.0 g was weighed and loaded into the reactor for in-situ reduction. First, nitrogen was pre-flowed for 30 min, and then the volume ratio of hydrogen to nitrogen was 1:4. The reduction temperature was 180 ° C and the time was 2 h. After the reduction was completed, the temperature was raised to 350 ° C, and the raw material reaction was started. The molar ratio of N-ethylaniline to 1,2-cyclohexanediol was 7:1, and the raw material feed space velocity was 0.4 h -1 The evaluation conditions and results are shown in Table 1
[0192] Table 1 Catalyst preparation conditions and reaction yields obtained in Example
[0193]
[0194] Among them, the yield listed in Example 6 is the average yield of the product after the reaction for 12 hours. The yield listed in Example 10 is the average yield of the product after the reaction for 15 hours. The yield listed in Example 19 is the average yield of the product after the reaction for 20 hours, and the yields listed in the remaining examples are the average yields of the products per hour after the reaction for 8 hours. In Table 1, the content value of the surfactant refers to the molar ratio of CTAC to total metal ions in the mixed system; the content value of the auxiliary agent refers to the molar ratio of the auxiliary agent metal ions to copper ions in the mixed system.
[0195] As can be seen from Table 1, by comparing Examples 1 to 3, it was found that when the calcination temperature was changed, it was confirmed that the catalyst calcined at 700°C catalyzed the reaction of N-methylaniline and ethylene glycol to generate N-methylindole, the yield of N-methylindole was better (81%). Further, by comparing Examples 1, 4, and 5, it was found that when the molar ratio of the raw materials copper and aluminum was changed and the molar ratio of copper and aluminum was confirmed to be 1:2, the catalyst obtained catalyzed the reaction of N-methylaniline and ethylene glycol to generate N-methylindole, and the yield of N-methylindole was better (81%). Further, by comparing Example 1 and Example 6 to Example 8, it was found that when the solvent composition and content were changed, it was confirmed that when the solvent contained hexadecyltrimethylammonium chloride and the molar ratio of hexadecyltrimethylammonium chloride to total metal ions was between 0.03 and 0.06, the obtained catalyst catalyzed the reaction of N-methylaniline and ethylene glycol to produce N-methylindole, and the yield of N-methylindole (84% to 87%) was better than that of the catalyst obtained without hexadecyltrimethylammonium chloride in the solvent (81%). Further, by comparing Example 1 and Example 9 to Example 12, it was found that when the catalyst component contained an auxiliary metal, it was confirmed that Mg and Ni were added to the catalyst as auxiliary metals to have a better product yield.
[0196] Furthermore, in Examples 19 to 24, the auxiliary metal selected was Mg, the molar ratio of the raw materials copper and aluminum in the mixed system during preparation was 1:2, the molar ratio of CTAC to total metal ions was 0.06, and the catalyst obtained when the sintering temperature was selected to be 700°C was used to prepare N-methylindole, indole, 3-methylindole and carbazole, respectively. It was found that the catalyst had a higher yield when used to prepare N-methylindole from N-methylaniline and ethylene glycol and to react aniline and 1,2-cyclohexanediol to generate carbazole.
[0197] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification.
[0198] For the method embodiments, for the sake of simplicity, they are all described as a series of action combinations, but those skilled in the art should know that the present invention is not limited by the order of the actions described, because according to the present invention, some steps can be performed in other orders or simultaneously. Secondly, those skilled in the art should also know that the embodiments described in the specification are all preferred embodiments, and the actions and components involved are not necessarily required by the present invention.
[0199] The above is a detailed introduction to a supported catalyst, a preparation method and its application in the synthesis of indole, carbazole and derivatives provided by the present invention. Specific examples are used herein to illustrate the principle and implementation mode of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for a person skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation mode and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. An application of a supported catalyst, characterized in that: The supported catalyst is formed by supporting CuO and an optional promoter metal on copper aluminum spinel, wherein the promoter metal is Mg, Zn, Ce, Zr, Mo, La, Y, Cr, Ni or Co; The supported catalyst is used as a catalyst for synthesizing indole or N-methylindole by the alcoholamine method; in the reaction raw materials for synthesizing indole or N-methylindole by the alcoholamine method, the molar ratio of amine to alcohol is 3:1 to 9:1, the raw alcohol is ethylene glycol, and the raw amine is aniline or N-methylaniline; The preparation method of the supported catalyst comprises: Dissolving a copper precursor, an aluminum precursor, and an optional auxiliary metal precursor in a solvent in a certain proportion to form a mixed system; Adding alkaline solution to the mixed system, adjusting the pH of the system to 9-11, aging for 12 h-24 h, collecting the solid by centrifugation, washing and drying to obtain a catalyst precursor; Grinding the catalyst precursor, placing it in a muffle furnace, and calcining it at 600° C. to 700° C. for 1 h to 6 h to obtain the supported catalyst; The copper precursor is Cu(NO3)2•3H2O; the aluminum precursor is Al(NO3)3•9H2O; the auxiliary metal precursor is a soluble salt containing Mg, Zn, Ce, Zr, Mo, La, Y, Cr, Ni or Co; In the supported catalyst, when the mass proportion of the auxiliary metal is 0, the mass proportion of CuO is 15% to 30%; the mass proportion of the copper-aluminum spinel is 70% to 85%; When the mass proportion of the auxiliary metal is 0.4% to 7%, the mass proportion of CuO is 18% to 25%; the mass proportion of the copper-aluminum spinel is 68% to 78%; In the mixed system, the molar ratio of copper ions to aluminum ions is 1:
2.
2. The use of a supported catalyst according to claim 1, characterized in that: In the mixed system, the concentration of total metal cations is 0.25 mol / L to 2 mol / L.
3. The use of a supported catalyst according to claim 1, characterized in that: The solvent is deionized water, or the solvent is an aqueous solution containing hexadecyltrimethylammonium chloride.
4. The use of a supported catalyst according to claim 3, characterized in that: In the mixed system, the molar ratio of the hexadecyltrimethylammonium chloride to the total metal cations is 0.03-0.1:
1.
5. The use of a supported catalyst according to claim 1, characterized in that: The soluble salts include nitrates, sulfates, acetates or chlorides.
6. The use of a supported catalyst according to claim 1, characterized in that: The alkali solution is sodium carbonate solution, sodium hydroxide solution or ammonia solution.
7. The use of a supported catalyst according to claim 1, characterized in that: The process conditions for synthesizing indole or N-methylindole by the alcohol amine method include: a reaction temperature of 250°C to 330°C; a reaction raw material feed space velocity of 0.1 h -1 ~2.0h -1 .
8. The use of a supported catalyst according to claim 1, characterized in that: Before introducing the reaction raw materials, the supported catalyst loaded into the reactor is reduced and activated at 150° C. to 200° C. for 1 h to 3 h in a nitrogen and hydrogen mixed atmosphere containing 1% to 20% hydrogen.
Citation Information
Patent Citations
Load-type copper oxide-based catalyst containing auxiliary agent and preparation method thereof
CN107252690A
Cu-based spinel type catalyst for preparing methanol through carbon dioxide hydrogenation as well as preparation method and application thereof
CN113663678A
Method for co-producing indole and 1, 2, 3, 4-tetrahydrocarbazole
CN118546082A